Analisis Pola Pemasaran Dalam Bisnis Dropshipping Dalam Meningkatkan Penjualan Online Pada Toko Hikmah Collection Kraksaan - Malia, Umi; Nuntufa, Nuntufa; Nikmatul, Nailin (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
This study aims to analyze marketing patterns in the dropshipping business implemented by Toko Hikmah Collection Kraksaan to increase online sales. The object of this research is the marketing strategy used by stores to attract more consumers and increase competitiveness in the increasingly competitive e-commerce industry. This study uses a qualitative method with a descriptive approach. Data is collected through interviews, observations, and documentation analysis to understand the marketing strategies implemented and their effectiveness in significantly increasing sales. The results of the study show that Toko Hikmah Collection Kraksaan uses various digital marketing strategies, such as social media, paid advertising, collaboration with micro-influencers, and promotions in the form of attractive discounts and free shipping. Customer testimonials are also used to build trust and increase customer loyalty. However, the store faces major challenges in the form of stiff competition and dependence on key suppliers. In conclusion, marketing strategy plays an important role in increasing online sales. For more optimal results, it is recommended that stores optimize digital content and expand marketing through various leading e-commerce platforms. Keyword: Digital Marketing, Dropshipping, Promotion Strategy, Online Sales.